Pengaruh Pondok Pesantren Darussalam Al-Waliyyah Terhadap Ekonomi Masyarakat Desa Blang Poroh Kecamatan Labuhan Haji Barat, Aceh Selatan (1980-2020) - Aswira, Herdi; Ibrahim, Husaini (Universitas Syiah Kuala, 2025)
The economic progress of a region in Indonesia is often caused by an institution, be it an educational institution or other institutions. The openness of an institution to the surrounding community greatly influences the community's economy. The study entitled